2016
DOI: 10.18356/15e9a052-en
|View full text |Cite
|
Sign up to set email alerts
|

Tertiarization in Chile: Cultural inequality and occupational structure

Abstract: Tertiarization, or the shift to service economies with an increasing prevalence of non-manual occupations, has been identified as a central phenomenon in contemporary societies. With the purported numerical and political decline of traditional working-class sectors, the middle class has come to be seen in recent decades as the dominant one. This understanding of the way society has evolved has gone along with a growing interest in forms of social differentiation other than the occupational one of industrial so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…For example, Torche (2007) demonstrated that reading is very much influenced by education and income. In addition, Gayo et al (2009, 2013, 2016) and Gayo (2013) showed that there is a clear and positive association between levels of education and socio-economic grouping, on the one hand, and cultural participation, on the other.…”
Section: Determinants Of Participationmentioning
confidence: 92%
“…For example, Torche (2007) demonstrated that reading is very much influenced by education and income. In addition, Gayo et al (2009, 2013, 2016) and Gayo (2013) showed that there is a clear and positive association between levels of education and socio-economic grouping, on the one hand, and cultural participation, on the other.…”
Section: Determinants Of Participationmentioning
confidence: 92%
“…According to Subercaseaux (2016), in the 20th century, especially between 1970 and 1973, the role of the state in the successful promotion of cultural policies was fundamental in the burgeoning humanist and artistic disciplinary fields. In this regard, Chile's profound socioeconomic inequality (Rodríguez-Weber, 2017) has had important cultural repercussions that are reflected in the differentiated adaptation to global culture among high-income versus lowincome socioeconomic groups, which has been a barrier to the expansion of a potential middle class (Gayo et al, 2016). Regarding the latter, the study of Gayo et al (2016) study is an example of the application of a positivist cultural study methodology although it was aimed to establish potential correlations between cultural and economic aspects rather than provide an index of culture.…”
Section: Chile On Cultural Developmentmentioning
confidence: 99%
“…In this regard, Chile's profound socioeconomic inequality (Rodríguez-Weber, 2017) has had important cultural repercussions that are reflected in the differentiated adaptation to global culture among high-income versus lowincome socioeconomic groups, which has been a barrier to the expansion of a potential middle class (Gayo et al, 2016). Regarding the latter, the study of Gayo et al (2016) study is an example of the application of a positivist cultural study methodology although it was aimed to establish potential correlations between cultural and economic aspects rather than provide an index of culture. Another interesting effort was made in 2011 in an extensive report by the National Council for Culture and the Arts ( 2016), which attempted to identify the contributions of cultural activities to the national economy.…”
Section: Chile On Cultural Developmentmentioning
confidence: 99%